2009
DOI: 10.1007/s12185-009-0443-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M and leukemia inhibitory factor increase hepcidin expression in hepatoma cell lines

Abstract: Overproduction of hepcidin by interleukin-6 (IL-6) is considered to be the main factor responsible for the development of anemia in inflammatory conditions. Since oncostatin M (OSM), a member of the IL-6 family, plays an important role in immune and inflammatory responses, we assessed the effect of OSM on hepcidin expression, as well as that of leukemia inhibitory factor (LIF), another member of the IL-6 family. We found that hepcidin expression was markedly induced by OSM and LIF in a time- and dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Pro-inflammatory properties of OSM were reported in the skin, adipose tissue, lung, heart and liver [32], [33], [34], [35], [36]. In contrast, other studies demonstrated anti-inflammatory effects of OSM, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Pro-inflammatory properties of OSM were reported in the skin, adipose tissue, lung, heart and liver [32], [33], [34], [35], [36]. In contrast, other studies demonstrated anti-inflammatory effects of OSM, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…OSM is known as an alternate cytokine that is able to regulate hepcidin gene expression 24,25 and LIF can regulate hepcidin expression. 24 In the anemia of multiple myeloma, increased levels of BMP-2 stimulate hepcidin expression. 26 Therefore, we also investigated whether CO could down-regulate hepcidin expression elicited by these inflammatory mediators.…”
Section: Co Inhibits Hepcidin Expression By Il-6 and Er-stress Inducersmentioning
confidence: 99%
“…Published work has shown that OSM regulates LDLR in liver cells [90] suggesting a role in cholesterol metabolism. More recent studies have identified hepcidin as a target for regulation by OSM [91, 92] resulting in decreased serum iron levels and implicating OSM in disorders involving anaemia.…”
Section: Effects On Hepatocytes and Livermentioning
confidence: 99%